Etching of unmodified Au@Ag nanorods: a tunable colorimetric visualization for the rapid and high selective detection of Hg2+. Issue 124 (30th November 2015) - Yang, Rong; Song, Dan; Wang, Chongwen; Zhu, Anna; Xiao, Rui; Liu, Jingquan; Long, Feng
Abstract : A simple and cost-effective colorimetric approach based on unmodified Au@Ag nanorods (Au@Ag NRs) was developed for Hg 2+ detection. Abstract : A simple and cost-effective colorimetric approach based on unmodified Au@Ag nanorods (Au@Ag NRs) was developed for Hg 2+ detection. Unmodified Au@Ag NRs with different Ag nanoshell thicknesses served for the signal readout because the Ag coating-induced a blueshift and enhancement of the longitudinal plasmon of Au NRs, resulting in abundant and tunable optical absorptions in the visible region. The etching sensing mechanism was revealed to be related to the redox reaction between Hg 2+ and the Ag nanoshell of the Au@Ag NRs. The Ag nanoshell of the Au@Ag NRs was gradually etched from the ends as the Hg 2+ concentration was gradually increased, and shoulder shapes were formed, and then disappeared. The Hg 2+ concentration-dependent color of Au@Ag NRs with a thick Ag nanoshell thickness changed from brownish-red to light-red, light-violet, and finally to colorless. The limit of detection (LOD) and the detection range of Hg 2+ became tunable as the Ag nanoshell thickness increased, and the lowest LOD was 10 nM. A dip located between two strong absorption peaks was observed when Au@Ag NRs with a thick Ag nanoshell thickness were used, and the change in this dip provided a new sensor parameter for Hg 2+ detection on the basis of absorption spectra. The proposed method also showed a high selectivity toward Hg 2+ over other metal ions. The Au@Ag NR detection system could detect even low Hg 2+ concentrations in drinking water.